Penggunaan Alat Penyerut untuk Meningkatkan Produksi Kerajinan Bambu pada Kelompok Pengrajin di Kota Tomohon - Zuldesmi Zuldesmi; Robert R. Winerungan (Universitas Negeri Makassar, 2018)
Tomohon is a city that has many people craft’s industries and one of them is a bamboo craft industry inKinilow village. In this place, the production process of woven bamboo which starting from cutting down, skinning,breaking until depleting processes is still traditional or manual by using machete and knife. As a result, the productperformance has a low quality because there is un-uniforming a product size (especially in the thickness) and form.In order to solve that problem, in this activity, we apply a bamboo depletion machine to increase the quantity andquality of bamboo depletion production for bamboo crafts. Bamboo depletion machine is a machine that works toattenuate bamboo with the thickness that can be arranged as needed. This machine is used to help smallentrepreneurs produce bamboo depletion products in large quantities by saving time and labor. The results show thatthis bamboo depletion machine has an average capacity of 550-650 layers/hour (about five times higher than manualprocess). So that, the productivity and quality of products made of bamboo can be improved and uniform accordingto consumer’s standards. Besides, tiredness and pains of workers can be released by using a bamboo depletionmachine.